2020
DOI: 10.3390/genes11020199
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Genomic and Transcriptomic Alterations in a Morphologically Stable Line, MU1, Generated by Intergeneric Pollination

Abstract: Interspecific hybridization creates genetic variation useful for crop improvement. However, whether pollen from a different genus affects the genomic stability and/or transcriptome of the recipient species during intergeneric pollination has not been investigated. Here, we crossed japonica rice cv. Z12 with the maize accession B73 (pollen donor) and obtained a morphologically stable line, MU1, exhibiting moderate dwarfism, higher tiller number, and increased grain weight compared with Z12. To reveal the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 58 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Inactivation of MMR (DNA mismatch repair system) genes that was observed was suggested as the cause of microsatellites' instability by failing to correct replication errors. Intergeneric cross between rice and maize was shown to bring about genomic rearrangements in the maternal parent even in the absence of evidence for introgression of the male parent (Meng et al, 2020). Intergeneric pollination was found to trigger extensive genomic changes in MU1, a morphologically stable line generated from the intergeneric cross of japonica rice cv.…”
Section: Molecular Changes In Incompatible Cross Derivativesmentioning
confidence: 99%
See 4 more Smart Citations
“…Inactivation of MMR (DNA mismatch repair system) genes that was observed was suggested as the cause of microsatellites' instability by failing to correct replication errors. Intergeneric cross between rice and maize was shown to bring about genomic rearrangements in the maternal parent even in the absence of evidence for introgression of the male parent (Meng et al, 2020). Intergeneric pollination was found to trigger extensive genomic changes in MU1, a morphologically stable line generated from the intergeneric cross of japonica rice cv.…”
Section: Molecular Changes In Incompatible Cross Derivativesmentioning
confidence: 99%
“…Some of these variations are agronomically useful and were evolved as additional source of variation (Meng et al, 2020;Visarada, 2020a;Wang et al, 2005Wang et al, , 2009. Meng et al (2020) obtained a morphologically stable line, MU1, exhibiting moderate dwarfism, higher tiller number and increased grain weight in rice  maize cross. Wang, Zhang, et al (2013) demonstrated that introgressive hybridization between Oryza sativa ssp.…”
Section: Progeny Studiesmentioning
confidence: 99%
See 3 more Smart Citations